Curating China's Cultural Revolution (1966–1976): CR/10 as a Warburgian Memory Atlas and Digital Humanities Interface. (Information & Culture, 2022)
CR/10 is a digital oral history platform that aims to collect and preserve cultural memories of China's Cultural Revolution (1966–76). With a rhetorical analysis of the design features and curation processes of the CR/10 website, this article discusses the functions of CR/10 as a Warburgian memory atlas that shape the nonlinear, multifaceted narratives of a historical incident. Alongside this rhetorical analysis, I also conducted three sets of user experience studies with over thirty participants both within and outside the academy, including an ethnographic conference observation, a virtual ethnography of an online book group, and several semi-structured interviews, to examine CR/10's usability and propose new design opportunities to empower the interface. This article offers a strong case for the datafication of cultural memories and contributes to digital archives and humanities interface design with an innovative theoretical lens.